Leading curriculum change: developing inquiry based teaching and learning in a primary school - Cullen, Lorraine Ann (2014)
Throughout my professional journey, I have encountered many thought provoking experiences which have, not only helped to shape my practice, but have also encouraged me to deeply question my purpose as a leader within education. Children growing up in the 21st century will encounter rapid change within their lives. The question that resonates deeply within me is what and how do we teach them today so that they are better prepared for tomorrow’s world? It is this concern that provides the impetus for this research.